LiDAR Principles, Processing and Applications in Forest Ecology - Guo, Qinghua; Su, Yanjun; Hu, Tianyu (Elsevier Science & Technology, 2023)
LiDAR Principles, Processing and Applications in Forest Ecology introduces the principles of LiDAR technology and explains how to collect and process LiDAR data from different platforms based on real-world experience.